From the virtual frontlines: law enforcement’s experience with social media in policing activities - Fortin, Francis (Journal of crime and justice, 2024)
Social media is increasingly used by both the public and police agencies. While numerous studies have documented the use of social media to communicate with the public, little research has focused on the use of social media in policing activities such as criminal intelligence and investigation. The objective of this research is to understand the use of social media in different policing activities by police in Canada. A questionnaire on the use of social media was completed by 177 members of six police organizations. Results show that social media is now an important tool for investigating crimes committed both online and offline. Gathering intelligence about organized crime, investigating runaways, and online crimes appeared to be the most widespread use of social media platforms and Facebook was the media most widely used during the period in which our study took place. Participants indicated that lack of knowledge of other social media, the use of Facebook by organized crime members, and having a personal Facebook account favored its use, despite the relevance of other platforms, such as YouTube or Twitter. Results highlight the need to improve training and efforts to maximize the potential of social media platforms to fight crime more efficiently.